Study of Mastoid Canals and Grooves in North Karnataka Human Skulls - Gavishiddappa Andanappa Hadimani; Ishwar Basavantappa Bagoji (Journal of Clinical and Diagnostic Research, 2013)
Introduction: This study was undertaken to observe the frequency of mastoid canals and grooves in north Karnataka dry human skulls. 100 dry human skulls of unknown age and sex from the department of Anatomy were selected and observed for the present study. Material and Methods: The mastoid regions of dry skulls were observed for the presence of mastoid canals and grooves, if any. A metallic wire was passed through the canal for its confirmation and then the length was measured. Results: The Mastoid canals were present in 53% of the total 100 skulls observed either bilaterally or unilaterally. Mastoid grooves were present in 18% of the total skulls (100) observed. Double mastoid canal was found in 01% of total skull studied and both Mastoid canals & Mastoid grooves together were present in 02% of the total skulls (100) observed. Conclusion: The knowledge of mastoid canals and grooves is very important for otolaryngologists and neurosurgeons. Because they contain an arterial branch of occipital artery with its accompanying vein which is liable to injury resulting into severe bleeding.